A novel integrated biomarker index for the assessment of hematological responses in MPNs during treatment with hydroxyurea and interferon‐alpha2. (17th October 2022) - Dam, Marc J. B.; Pedersen, Rasmus K.; Knudsen, Trine A.; Andersen, Morten; Ellervik, Christina; Larsen, Morten Kranker; Kjær, Lasse; Skov, Vibe; Hasselbalch, Hans C.; Ottesen, Johnny T.
Abstract: Background: Conventional cytoreductive therapy for patients with chronic Philadelphia‐negative myeloproliferative neoplasms (MPNs) includes hydroxyurea (HU), interferon‐alpha2 (IFN), and anagrelide. HU is worldwide the most used cytoreductive agent, which lowers elevated blood cell counts within days in the large majority of patients. However, some patients may experience rebound cytosis when HU is reduced due to cytopenia, thereby potentially giving rise to fluctuating cell counts during therapy. Such rapid oscillations may be harmful and potentially elicit thrombosis. Treatment with IFN gradually lowers elevated cell counts within weeks and when the dosage is reduced, the cell counts do not rapidly increase but are sustained within the normal range in the large majority of patients. Conventional hematological response criteria are among others based upon single absolute cell count values and do not take into account the relative decreases toward normal for each cell count. Materials, Methods & Results: Using serial data from the Danish DALIAH trial, we herein describe a novel integrated biomarker index for the assessment of hematological and molecular ( JAK2V617F ) responses in patients with MPNs during treatment with IFN or HU. Discussion: This novel tool convincingly displays the superiority of IFN versus HU in normalizing elevated cell counts. Our results need to be validated in larger studies but already now call for studies of the safety and efficacy of combination therapy during the initial treatment of patients with MPNs. Abstract : A Novel Integrated Biomarker Index for the Assessment of Hematological Responses during Treatment with Hydroxyurea and Interferon‐alpha2. This novel tool convincingly displays the superiority of interferon‐alpha2 versus hydroxyurea in normalizing elevated cell counts.